The Development of Social Attitudes Through Cooperative Learning Methods in Social Studies Education Subjects in Public Junior High School 1 Batang - Hardaningtiastuti, Hindah Wasis; Soegito, Ari Tri; Murwatiningsih, Murwatiningsih (JESS (Journal of Educational Social Studies), 2018)
The development of social attitudes through cooperative learning methods to improve the social attitudes of discipline, responsibility and cooperation in Public Junior High School 1 Batang is needed in the social studies learning a process which is caused by violations of the discipline of students by them. The purpose of this research is to analyze the planning, implementation, evaluation, and impact of the use of cooperative learning methods for the development of social attitudes in social studies education subjects at Public Junior High School 1 Batang. This research uses a qualitative approach. The research subjects were students of class VII Public Junior High School 1 Batang. Data collection research is carried out by observation, interview, and documentation techniques. Research data were analyzed by interactive data analysis models. The results of research that the development of social attitudes through cooperative learning methods in social studies education subjects were applied appropriately, both in planning according to the syllabus that had been developed, implementation supported by media and learning resources, and learning evaluation so as to create a fun, open, democratic and conducive learning atmosphere which has a positive impact on the development of discipline, cooperation and responsibility. The conclusion of this research is the development of social attitudes of students in social studies education learning seen from the teacher's process of arranging planning, implementing learning, evaluating so that it has a positive impact for class VII students in Public Junior High School 1 Batang for discipline, responsibility and cooperation in the form of habituation in class and school environment.